Value Added Tax Treatment On Health Services After Harmonization Of Tax Regulations Law - Nurcitra Amanda; Lazuardi Widyanto Pratama (Jurnal Akuntansi dan Perpajakan, 2023)
One of the changes related to Medical Health Services after the enactment of the VAT Cluster Law on the Harmonization of Tax Regulation is the provision of VAT exemption facilities for these services. This change is further regulated in Government Regulation no. 49 of 2022. This study aims to examine VAT on Medical Health Services after the enactment of the Law on the Harmonization of Tax Regulations and the policy implications of VAT exemption on medical health services for the community as the end consumer. The research method used in this research is descriptive qualitative with the use of secondary data. The results of this study conclude that service providers are obliged to be confirmed as Taxable Entrepreneur to collect VAT for people who do not use health services not borne by the government. However, Taxable Entrepreneur cannot credit its input tax.